Exploring drivers to engage in fashion luxury consumption - Loureiro, S. M. C.; Maximiano, M.; Panchapakesan, P. (Proceedings of the ICCMI 2017 - 5th International Conference on Contemporary Marketing Issues, 2017)
The main purpose of the current study is to analyze how desire, perceived-self, social values and involvement are related to consumer engagement into the fashion luxury industry. A sample of 295 luxury fashion consumers participate in the study. Findings suggest that perceived-self is not one of the most significant driver to consumer engagement. Subjective well-being may also act as an outcome of consumer engagement. The article also provides managerial implications, limitations and further research.